Petrological and geochronological constraints on the origin of the Palimé–Amlamé granitoids (South Togo, West Africa): A segment of the West African Craton Paleoproterozoic margin reactivated during the Pan-African collision - (:unkn) unknown (My University, 2007)
The Palimé–Amlamé Pluton (PAP) in southern Togo, consists of silica-rich to intermediate granitoids including enclaves of mafic igneous rocks and of gneisses. They are commonly called the “anatectic complex of Palimé–Amlamé” and without any convincing data, they were interpreted either as synkinematic Pan-African granitoids or as reworked pre Pan-African plutons. New field and petrological observations, mineral and whole-rock chemical analyses together with U–Pb zircon dating, have been performed to evaluate the geodynamic significance of the PAP within the Pan-African orogenic belt. With regard to these new data, the granitoids and related enclaves probably result from mixing and mingling processes between mafic and silicic magmas from respectively mantle and lower crust sources. They display Mg–calc-alkaline chemical features and present some similarities with Late Archaean granites such as transitional (K-rich) TTGs and sanukitoids. The 2127 ± 2 Ma age obtained from a precise U/Pb concordia on zircon, points out a Paleoproterozoic age for the magma crystallization and a lower intercept at 625 ± 29 Ma interpreted as rejuvenation during Pan-African tectonics and metamorphism. Based on these results, a Pan-African syn to late orogenic setting for the PAP, i.e. the so-called “anatectic complex of Palimé–Amlamé”, can be definitively ruled out. Moreover according to its location within the nappe pile and its relationships with the suture zone, the PAP probably represents a fragment of the West African Craton reactivated during the Pan-African collision.
Keywords: African Research